Odour nuisance from solid wastes: development of a model describing emission, dispersion and reception - Sarkar, Ujjaini (Cranfield University, 1999)
Odours emitted from Municipal Solid Waste (MSW) landfills create nuisance in the surrounding environment. The odour comes from the mixture of volatile organic compounds present in the landfill gas, leachate and leachate treatment systems, sewage sludges and waste materials. The research objective is to develop an Odour Impact Model (OIM) to quantify the impact of odour from a landfill on the surrounding communities. The model provides a basis for site planning and odour regulations. A suitable OIM has been developed with special emphasis on quantifying emissions from the source. A micrometeorological model has been developed based on the estimation of footprints of scalar odour concentration measurements in the atmospheric surface layer. A simple experiment has been designed based on this model. The results of this model have been compared with those from the direct emission measurement approach using a portable Lindvall Hood. Major advantages of the indirect micrometeorological approach are the simplicity of the experiment design, and its ability to cover various spatial resolutions. The commercial software MPTER/COMPLEX-I and UK-ADMS have been used to predict the dispersion of odour around two solid waste sites. UK-ADMS uses a better representation of short-range dispersion (considering plume meandering and in-plume fluctuations) and is thus likely to be more accurate close to the source. The two models compare well at distances greater than 500 metres downwind from the source. The perception recorded in the surrounding community has been analysed with four psychophysical models to validate the impacts predicted by the suitable dispersion model. The model based on Weber-Fechner law describes the relationship between odour intensity and odour concentration (ou/m3) very well for the less intense odour samples, while Laffort’s equation expresses a better relationship with more intense odour samples. The main strength of the integrated OIM is its ability to handle the problem of odour nuisance from solid wastes quantitatively. Amongst the major weakness was poor validation due to lack of sufficient data. Successful use of the OIM will require measurements which account for the extreme variations in surface conditions, cover type, waste composition, wasteage and subsidence.